A phytobiotic extract, in an aqueous or in a cyclodextrin encapsulated form, added in diet affects meat oxidation, cellular responses and intestinal morphometry and microbiota of broilers - Dokou, Stella; Mellidou, Ifigeneia; Savvidou, Soumela; Stylianaki, Ioanna; Panteli, Nikolas; Antonopoulou, Efthimia; Wang, Jing; Grigoriadou, Katerina; Tzora, Athina; Jin, Lizhi; Skoufos, Ioannis A.; Giannenas, Ilias (Frontiers in Animal Science, 2023)
The present trial examined diets supplemented with an extract including Greek oregano, garlic, rock samphire and camelina, either in aqueous form or encapsulated in cyclodextrin on broiler chickens. The duration of the trial was 35 days. Mixed broiler chicks (Ross-308, 120 individuals, one-day-old) were randomly allocated to three groups with four replicates. Control Group A (CONTROL) was fed basal diets based on maize and soybean meal. AQORGCC group was further supplemented with the aqueous herbal extract, while CDORGCC group with the cyclodextrin one. Lipid and protein oxidation was evaluated on breast and thigh meat samples. Furthermore, to address cellular stress and signaling responses, expression patterns of heat shock proteins (Hsp60, Hsp70, Hsp90), mitogen activated protein kinases (p38, p44/42 MAPKs) and apoptotic-related proteins (Bcl-2/Bad ratio) were investigated in breast and thigh tissues using Western Blot analysis. Intestinal morphometry was also assessed on duodenum, jejunum and ileum. To investigate ileal and cecal bacterial community diversity, 16S rRNA gene high-throughput amplicon sequencing on the V3-V4 hypervariable region was performed. The results showed that the herbal extract in cyclodextrin delayed meat lipid oxidation. According to the protein expression patterns, the formulated diets elicited tissue-specific cellular response. Compared to the control, the encapsulated form resulted in significant Hsps induction and MAPKs activation, while the aqueous form decreased or maintained most of the examined proteins at constant levels. Villus height and lamina propria width was mostly affected by the aqueous herbal extract, whereas the number of goblet cells remained unchanged among the groups. Firmicutes, Proteobacteria and Bacteroidota were the major phyla in mean relative abundance in all diets in both caecum and ileum samples. Alpha-diversity indices highlighted higher species richness and diversity in caecum versus ileum. Dietary mixtures of herbal extracts and particularly in the form of cyclodextrin, improved protein and lipid oxidation, and increased the number of beneficial lactic acid producing bacteria in caecum, while the aqueous herbal extract affected mostly bacteria in the proximal part of the intestine.